The Effectiveness of Technology for Improving the Teaching of Natural Science Subjects - Nawzad, Lezan; Rahim, Dana; Said, Karzan Wakil (Indonesian Journal of Curriculum and Educational Technology Studies, 2018)
This paper investigates the eï¬ectiveness of integrating technology with teaching method for science subjects. For this, the research was conducted in Shahid AbdulRazaq primary school in Sulaimania city-Iraq. Two methods were used for this investigation: A questionerâs form and testing method. The participant students were 50 students from grade 3 and 5. The results showed that studentâs preference for using technology in teaching science was 75% and 95% for both third and fifth grade. Also, the passing rate for the students of third and fifth grade using technology teaching method is 57% and 83% compared to 43% and 17% respectively when the traditional method used for teaching science subject. This research confrmed that teaching science subjects with technology increased the studentâs interest in the learning process and improved the studentâs achievement scores and also helped the students to do their homework more easily compared to the traditional teaching methods. Abstrak Artikel ini mengindentifkasi keefektivan integrasi teknologi dalam metode pembelajaran mata pelajaran sains. Penelitian ini dilaksanakan di sekolah dasar Shahid Abdul-Razaq, Kota Sulaimania, Iraq menggunakan 2 (dua) instrument, yaitu kuesioner dan tes. Responden penelitian ini melibatkan 50 (limapuluh) siswa kelas 3 (tiga) dan 5 (lima). Hasil penelitian menunjukkan bahwa minat siswa dalam menggunakan teknologi dalam pembelajaran sains sebesar 75% dan 95% untuk kelas tiga dan lima. Selain itu angka kelulusan siswa kelas tiga dan lima ketika menggunakan teknologi untuk menunjang pembelajaran sebesar 57% dan 83%, berbeda dibanding ketika menggunakan metode tradisional, yakni sebesar 43% dan 17% juga untuk kelas tiga dan lima pada mata pelajaran sains. Penelitian ini menegaskan bahwa pembelajaran sains yang ditunjang teknologi terbukti dapat meningkatkan minat siswa dalam pembelajaran dan meningkatkan capaian hasil belajar siswa, selain itu juga membantu siswa dalam mengerjakan pekerjaan rumah lebih mudah disbanding ketika sekadar menggunakan metode tradisional. Keywords: Educational technology; natural science; traditional teaching method